The Influence of Islamic Religious Education on the Student's Conduct - Imam Tabroni; Akbar Miftahur Romdhon (PT FORMOSA CENDEKIA GLOBAL, 2022)
SMPIT Kharisma Darussalam is an Islamic educational institution that is expected to be able to produce the seeds of a generation of Muslims who can carry out Islamic religious orders properly and correctly, from which a learning process must be built in the classroom and outside the classroom that can shape the morals of students and students with good morals. good. This study also aims to examine how much influence the role of Islamic religious education learned in schools has on the morals of students at SMPIT Kharisma Darussalam and to find out what efforts are made by schools in improving the morals of students at SMPIT Kharisma Darusslam. This research method uses a qualitative descriptive method by means of a case study. The results of this study are that there is a change in the morals of students at SMPIT Kharisma Darussalam.